Taxonomy on library and information science - Aguado, Chely Jon O. (2003)
Classification of the rapidly expanding world of information into an organized scheme of things is becoming more and more the burden of the library profession. While the task at hand falls on the information specialists, the Institute of Library and Information Science, University of the Philippines, Diliman has very limited studies devoted to designing classification systems. Thus, the absence of such studies prompted the development of this study in producing a taxonomy of terms on Library and Information Science that proves to be one of the many tools that are helpful to information scientist.